Ultrathin Solar Cell With Magnesium-Based Optical Switching for Window Applications - Gotz-Kohler, Maximilian; Meddeb, Hosni; Gehrke, Kai; Vehse, Martin; Agert, Carsten (IEEE journal of photovoltaics, 2021)
Photovoltaic windows that can be switched between transparent and energy harvesting mode can be realized by using ultrathin solar absorbers embedded in an optical nanocavity. In the present work, we use a 5 nm thick amorphous germanium absorber integrated in a magnesium-based thin film optical cavity, which switches from an absorptive to a transparent state due to hydrogen absorption. We analyze the influence of the mirror layer thickness on the light absorption, photocurrent generation, and transmission as well as color neutrality of the device. The optical properties are studied by 1-D transfer-matrix method by changing Mg thickness between 0 and 100 nm, then compared to the experimental results of fabricated devices. When the thickness of Mg increases, the switchable average transparency varies between 25% and 0%, while the power conversion efficiency rises up to 2.3%. The applicability of the device is tested by modeling the annual power generation in realistic scenarios. The influence of the cardinal orientation and the seasons on the switchable photovoltaic window implemented in a building facade with the abovementioned parameters is analyzed for different switching scenarios.